2000
DOI: 10.1136/vr.146.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study of clinical complications occurring after arterial punctures in 111 dogs

Abstract: The clinical complications occurring after 111 dogs had undergone arterial punctures were reviewed in relation to the dogs' breed, bodyweight, age, sex and underlying diseases. Seven of the dogs had moderate to extensive ecchymoses, which were significantly more common in dogs under 3.5 kg in bodyweight and in dogs with disorders of the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…One study that reviewed a series of 111 arterial punctures in dogs reported a possible association between increased risk of bleeding and cardiovascular disease, and 4 of 7 dogs with bleeding complications had cardiovascular disease. 24 Several studies have found good correlation between bleeding time and CT. 11,40,41 Very high CT (Ͼ200 seconds) with ColϩADP as agonist might therefore be a risk factor for bleeding in dogs with MR. 42 Activated platelets are known to release inflammatory mediators that can cause vascular changes, and a relationship appears to exist between activated platelets and conditions such as atherosclerosis, thrombosis, and intimal hyperplasia in humans. [43][44][45] Vascular changes resembling those found in the mitral valves have been described in CKCS, 16,17 and we have found that clinical signs compatible with small cerebral emboli are more common in breeds predisposed to MMVD than in dogs in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that reviewed a series of 111 arterial punctures in dogs reported a possible association between increased risk of bleeding and cardiovascular disease, and 4 of 7 dogs with bleeding complications had cardiovascular disease. 24 Several studies have found good correlation between bleeding time and CT. 11,40,41 Very high CT (Ͼ200 seconds) with ColϩADP as agonist might therefore be a risk factor for bleeding in dogs with MR. 42 Activated platelets are known to release inflammatory mediators that can cause vascular changes, and a relationship appears to exist between activated platelets and conditions such as atherosclerosis, thrombosis, and intimal hyperplasia in humans. [43][44][45] Vascular changes resembling those found in the mitral valves have been described in CKCS, 16,17 and we have found that clinical signs compatible with small cerebral emboli are more common in breeds predisposed to MMVD than in dogs in general.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 The decreased platelet reactivity found in humans and dogs with severe valvular disease might be associated with increased bleeding tendency during surgical procedures. [22][23][24] The Platelet Function Analyzer (PFA-100) a evaluates platelet function in anticoagulated whole blood flowing under high shear through a capillary and an aperture in a membrane coated by agonists. The instrument measures the time it takes before a platelet plug occludes the membrane aperture.…”
mentioning
confidence: 99%
“…Blood pressure was recorded using an oscillometric device. c Additionally, PCV, hemoglobin (Hgb), total plasma protein (TPP), pH, HCO 3 − , base excess (BE), and lactate were concurrently recorded from results measured using the arterial blood sample.…”
Section: Methodsmentioning
confidence: 99%
“…Blood sampling for repeated blood gas analysis is also stressful and uncomfortable for human patients requiring multiple punctures if indwelling catheters are not placed . Likewise, arterial blood sampling is technically challenging or impossible in very small or young animals and complications related to arterial puncture are reported in small dogs . Because PO 2 and PCO 2 measurements are required to make decisions regarding the need for oxygen supplementation or mechanical ventilation, a reliable method to measure these variables in small animals is essential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation